Relationship of the Circulating Endothelial Progenitor Cells to the Severity of a Coronary Artery Lesion in Unstable Angina - Cheng Xiao; Lixiang Liu; Xi Li; Xiaoan Yang; Hanxiong Liu (Cardiology Research and Practice)
The number and function of circulating endothelial progenitor cells (EPCs) decreased in stable coronary artery disease. Nevertheless, there were few studies that explored the variation of EPC and the relationship with the severity of coronary artery lesions in unstable angina (UA). Therefore, this leaves an area for the investigation of the difference in the number and activity of circulating EPCs and the relationship with the Gensini score in unstable angina. Fluorescence-activated cell sorter analysis, as well as DiI-acLDL and lectin fluorescent staining measure the number of circulating EPCs. The transwell chamber assay and MTT were evaluated by the migration and proliferation of circulating EPCs. In addition, the flow-mediated dilation (FMD), Gensini score, and IL-6 levels in plasma were determined. We found that UA patients had the higher number and lower function of circulating EPCs. With the increase in severity of coronary artery lesions, the migration and proliferation of EPCs were decreased. Moreover, the function of the circulating EPCs was negatively associated with severity of coronary artery lesions in unstable angina. In addition, UA patients presented elevated IL-6, which was negatively correlated with the function of circulating EPCs and FMD and positively correlated with the severity of coronary artery lesions evaluated by the Gensini score. These findings revealed the decline in the function of circulating EPCs was associated with the severity of coronary artery disease, which may be related to systemic inflammation.